2021
DOI: 10.1021/acs.jpcb.1c01327
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Phase Separation in Ternary Mixture Ionic Liquid Electrolytes

Abstract: We investigate the phase behavior of ternary mixtures of ionic liquid, organic solvent, and lithium salt by molecular dynamics simulations. We find that at room temperature, the electrolyte separates into distinct phases with specific compositions; an ion-rich domain that contains a fraction of solvent molecules and a second domain of pure solvent. The phase separation is shown to be entropy-driven and is independent of lithium salt concentration. Phase separation is only observed at microsecond time scales an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 103 publications
5
19
0
Order By: Relevance
“…Upon phase separation, the electrolyte mixture separates into two domains, one domain containing the organic solvent G4 and another domain containing a mixture of G4 and ionic species (termed the ionic domain). This is consistent with our previously reported results of a ternary mixture of [EMIM][BF 4 ] IL, G4, and [NO 3 ] salt. , The composition of the ionic domain varies as a function of temperature. By increasing temperature, the ionic domain becomes more condensed with ions by expelling G4 molecules.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Upon phase separation, the electrolyte mixture separates into two domains, one domain containing the organic solvent G4 and another domain containing a mixture of G4 and ionic species (termed the ionic domain). This is consistent with our previously reported results of a ternary mixture of [EMIM][BF 4 ] IL, G4, and [NO 3 ] salt. , The composition of the ionic domain varies as a function of temperature. By increasing temperature, the ionic domain becomes more condensed with ions by expelling G4 molecules.…”
Section: Resultssupporting
confidence: 93%
“…Table S1 shows the number of molecules in each system, and a list of the simulations is summarized in Table S2. Our previous studies show that for systems of comparable size, 300 ns is enough to observe initial stages of phase separation. , This is consistent with other studies in which it is reported that structures like ion pairs and ion clusters take a few hundred nanoseconds to form. Figure shows a snapshot of all the simulated ternary electrolyte mixtures and their corresponding temperature and duration of the simulation. In all but two of the systems, we observed a phase transition between the initial homogeneous system and a demixed system with two coexisting domains.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…While in an aprotic IL the cation is preferentially coordinated by the anion, in a protic IL proton competition for TFSIcoordination can leave the Li + cations more free, resulting in higher conductivity and lower charge transfer resistance, implying the possibility to operate at higher discharge rate [10,36,37]. Changing the anion [44,55],…”
mentioning
confidence: 99%